Social Media Etiquette Among Healthcare Professionals [20G]. Issue 1 (May 2017) - Davis, Jay; Folse, Katherine; Billiot, Angelle; Bissonnette, Rosella; Hagan, Joseph; Stafford, Irene
Abstract : INTRODUCTION: Social media (SM) use among healthcare professionals (HCPs) has skyrocketed. It is uncertain whether HCPs, including medical students, residents, and attending physicians, are aware of appropriate SM conduct. This study was conducted to survey HCPs on SM practices and knowledge of SM policy. METHODS: A survey was conducted among HCPs pertaining to SM usage that included reasons for use and applicable policy. The chi-square test was used to compare different occupations' proportion of SM use, awareness of the AMA policy regarding SM and the proportion having received lectures regarding appropriate use. SAS version 9.4 was used for analysis. A 5% significance level was used for hypothesis tests. RESULTS: Six hundred forty-six participants responded: 524 (81%) medical students, 91 (14%) residents, 25 (4%) attending-physicians, and 6 (1%) unknown. Ninety-eight percent of participants stated they used SM. Only 33% were aware of the AMA SM policy and 43% received prior education on SM usage. The proportion of respondents reporting that they use SM more than 2 hours per week differed significantly by occupational group (p = 0.002) with attendings least likely to do so (41% compared to 71% for all others). A significantly smaller proportion (p < 0.001) of students(28%) were aware of the AMA policy compared to residents(56%) and attendings(63%). Students were also less likely (p < 0.001) to have received lectures regarding appropriate SM use compared to residents(64%) and attendings(54%). CONCLUSION: Our study demonstrated that medical students were more likely to use SM but were least likely to receive information on SM policy, a potential gap in medical education.